ESCREVIVÊNCIA, TESTIMONY, AND HUMAN RIGHTS IN CONCEIÇÃO EVARISTO'S OLHOS D'ÁGUA - Cristina Ferreira Pinto-Bailey (Revista Brasileira de Literatura Comparada, 2021)
Informed by critical studies on human rights literature, testimonial literature, and (auto-) biographical narrative, this essay analyzes stories from Conceição Evaristo’s Olhos d’água (2014), with the purpose of examining the role narrative fiction may play as a form of testimony and resistance literature that gives voice to those normally silenced by racial and economic oppression. Evaristo characterizes her work as escrevivência, a type of writing originated from the subject’s personal experiences; this subject is mostly Black poor women with whom the narrative voice identifies. Thus, her work presents characteristics of autographic and testimonial literature that seeks to denounce the violation of Brazil’s Black population’s human rights.